Rapid Water Quality Assessment as a Quick Response of Oil Spill Incident in Coastal Area of Karawang, Indonesia - Effendi, Hefni; Mursalin, Mursalin; Hariyadi, Sigid (Frontiers in Environmental Science, 2022)
The purpose of this study was to assess the effect of oil spills on seawater quality along the coastal waters of Karawang Regency. Several laboratories were involved in measuring water quality to get representativeness of the location of the exposed waters both spatially and temporally. The measurement of seawater quality was carried out in situ and in the laboratory. Seawater quality data were compared with quality standards and discussed descriptively. All key water quality parameters (total petroleum hydrocarbon, polycyclic aromatic hydrocarbon, phenol, MBAS, and oil and grease) were below the detection limit of equipment, and a number of metals generally met quality standards. Only shortly after the oil spill in the vicinity of the spill source, the Ni metal exceeded the quality standard. However, after some time, spatially and temporally Ni has met the quality standard. Parameters not related to oil spills such as total phosphate generally did not meet quality standards. This might be related to the high activity on land, such as waste from domestic, industry, and agricultural activities entering coastal waters. Based on intertemporal data, the effect of an oil spill on water quality was temporary. This shows that the handling of the impact of the oil spill has shown good results and the quality of seawater remained quite good. Oil spills that float on the ocean surface were picked up, and those that washed ashore were cleaned up and collected.